EVALUASI KINERJA SIMPANG BERSINYAL EMPAT LENGAN PADA SIMPANG INPRES KOTA LHOKSEUMAWE - Gustina Fitri; Rosalina Rosalina; M. Arif Munandar (Politeknik Negeri Lhokseumawe, 2016)
Lhokseumawe Inpres intersection consists of 4 approaches, which serve as a vehicle to change the direction of movement. The purpose of this study is to know the performance of signaled intersections on any approach to the degree of saturation based on current capacity using the Indonesian Road Capacity Manual (MKJI). The research was conducted for 3 days from 06.30 - 18.00 divided over 3 time based on the graph of the rush hour fluctuation with traffic survey method. The field survey was conducted using hand tally counter. Based on the results of the study, obtained peak volume of 1370.16 smp / hour with a capacity value of 896.2 pcu / hour, the degree of saturation obtained by 0.654 where the condition is close to saturation.Keywords: Intersection, cycle time, signal phase, capacity, degree of saturation.